Effects of antioxidant nutrients on muscle mass, strength and function in COPD patients: A meta-analysis of randomized controlled trials. - Qinman He; Pan Yang; Ye Wang; Wanmei Xu; Yi Feng; Fei Xie; Guixiang Xu (PLoS ONE)
Aim To comprehensively investigate the effects of antioxidant nutrients on muscle mass, strength and function in chronic obstructive pulmonary disease (COPD) patients. Methods PubMed, Embase, Cochrane Library, and Web of Science were comprehensively searched from the inception to January 3, 2024. The quality of randomized controlled trials (RCTs) was measured using the Jadad scale. Weighted mean differences (WMDs) and 95% confidence intervals (CIs) were used as the effect size for measurement data. Further, subgroup analysis was conducted based on whether patients participated in lung rehabilitation plans while receiving nutritional interventions. Sensitivity analysis was performed on all outcomes. Results A total of 12 studies involving 595 patients with COPD were included, with 11 studies had high quality, and one study had low quality. For muscle mass, patients receiving antioxidant nutrients had a significantly increased lean body mass index compared with those not receiving antioxidant nutrients (pooled WMD: 0.903, 95% CI: 0.264, 1.541, P = 0.006). For patients who did not participate in lung rehabilitation plan while receiving nutritional interventions, antioxidant nutrients brought about a significantly higher lean body mass index (pooled WMD: 1.360, 95% CI: 0.560, 2.160, P = 0.001). For muscle strength, patients in the antioxidant nutrient intervention group had significantly higher hand grip strength (HGS) than those in the non-antioxidant nutrient intervention group (pooled WMD: 1.976, 95% CI: 1.337, 2.615, P < 0.001). Patients receiving antioxidant nutrients had significantly greater inspiratory muscle strength (MIP) than those not receiving antioxidant nutrients (pooled WMD: 8.127, 95% CI: 2.677, 13.577, P = 0.003). Conclusion Antioxidant nutrient intervention significantly improved HGS, MIP and lean body mass index in COPD. Clinicians should consider increasing food intake or supplementation rich in antioxidants in the treatment plan of patients with COPD.